2016
DOI: 10.1097/mej.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous dexamethasone in acute management of vestibular neuritis: a randomized, placebo-controlled, single-blind trial

Abstract: The value of dexamethasone cannot be established, given the small sample and limitations of the present study. Some observations consistent with clinical improvement cannot exclude a true treatment effect, and further study is still warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Thus, 17 full articles were assessed for eligibility. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Two further records had to be excluded due to inconsistency of the inclusion criteria. 32,33 Finally, 15 studies were included in the quantitative and qualitative analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, 17 full articles were assessed for eligibility. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Two further records had to be excluded due to inconsistency of the inclusion criteria. 32,33 Finally, 15 studies were included in the quantitative and qualitative analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…As the studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] showed different outcome criteria, a re-coding was performed forming a composite endpoint. The following criteria were judged as good clinical outcome event in the acute phase (Outcome I):…”
Section: Evaluation Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of the corticosteroid intervention ranged from 1 to 21 days. The most common corticosteroids used were dexamethasone 21,22,26 and methylprednisolone. 13,23,25 Records idenƟfied through database searching (n = 1375) Treatment: (n = 51) dexamethasone 12 mg (IV), diazepam 10 mg in 500 mL of 0.9% saline (IV), and thiethylperazine 6.5 mg subcutaneously.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Vestibular rehabilitation training can accelerate the recovery of patients with acute vestibular neuritis and reduce the disability degree of patients with permanent vestibular injury. It has a certain positive effect on the longterm recovery of patients as well as the recovery of balance function (14,15). Training methods mainly include fixation stability visual tracking training, static and dynamic posture stability training, and functional activity training (16).…”
Section: Introductionmentioning
confidence: 99%